Study of the Impact of Rainfall Pattern Dynamics on Carbon Monoxide and Nitrogen Dioxide Using Cloud Computing (Case Study in the Special Region of Yogyakarta, Indonesia) - Sejati, Sadewa Purba; Neritarani, Rivi (Faculty of Geography, Universitas Gadjah Mada, 2025)
Carbon monoxide (CO) and nitrogen dioxide (NO2) are the primary pollutants found in the air. Based on the results of the study of predecessor researchers, it is known that human activity factors cause spatial and temporal changes in primary pollutants in the air, while natural factors, such as rainfall changes during the transition of seasons, have not been studied further. This study was conducted to examine the impact of rainfall changes on spatial patterns of primary pollutants (CO and NO2). The Special Region of Yogyakarta (DIY), Indonesia was chosen as a research area. The data used were remote sensing data, namely CHRIPS (Climate Hazards Group InfraRed Precipitation with Station data, NRTI (Near Real Time) / L3_CO data, and NRTI / L3_NO2 data. The data were analyzed using cloud computing methods based on Google Earth Engine and statistical analysis. The results showed that the dynamics of rainfall patterns had an impact on changes in CO and NO2 concentrations although it was not significant. Based on the study, it is known that an increase in rainfall of 1% causes a decrease in CO concentration of 1.935 x 10-5 mol/m2 and a decrease in NO2 concentration of 3.151 x 10-9 mol/m2. A study conducted in southern India also concluded that higher rainfall has the potential to reduce CO and NO2 concentrations. The impact of rainfall pattern dynamics presented quantitatively in this study is a new finding, because there have not been many studies that explain the impact of rainfall pattern dynamics on CO and NO2 quantitatively.Received: 2024-08-24 Revised: 2025-01-02 Accepted: 2025-02-16 Published: 2025-05-26